ADVERSE EFFECTS OF PREMATURITY IN EARLY CHILDHOOD OF CHILDREN FROM PLEVEN, BULGARIA - Kamburova, Mariela (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Prematurity has a negative impact on physical development and health by increasing the demand of health and social services in early childhood of preterm children.